Foreign Direct Investment in Nigeria as an Emerging Market - Binuyo, Babatunde O.; Phyl-Arhedo, Onosetale E.; Ocharive, Aruoriwo C. (NIU Journal of Social Sciences, 2018)
The study investigated â€œForeign direct investment in Nigeria as an emerging marketâ€. Time series data collected from the World Bank and the Central Bank of Nigeria (CBN) Statistical Bulletin between periods of (1986-2016) was used to regress the model using the Autoregressive Distributed Lag Model (ARDL) technique. The ARDL showed a short run and long run relationship in the model. The economy adjusts back to equilibrium at 12%. Findings from the study showed that Foreign direct investment has a negative effect on the economy and this implies that incentives for foreign direct investment has not favoured Nigeria. Therefore, the government should create an enabling environment to encourage the growth of domestic investment in the country and also focus on the development of human capital and education as this will have a spill over effect on the economy as a whole. Keywords: Foreign direct investment, Emerging markets, Real gross domestic products.